2018
DOI: 10.1039/c7cp06158g
|View full text |Cite
|
Sign up to set email alerts
|

Hot kinetic model as a guide to improve organic photovoltaic materials

Abstract: The modeling of organic solar cells (OSCs) can provide a roadmap for their further improvement. Many OSC models have been proposed in recent years; however, the impact of the key intermediates from photons to electricity-hot charge-transfer (CT) states-on the OSC efficiency is highly ambiguous. In this study, we suggest an analytical kinetic model for OSC that considers a two-step charge generation via hot CT states. This hot kinetic model allowed us to evaluate the impact of different material parameters on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 114 publications
1
30
0
Order By: Relevance
“…Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state . A popular method to address this issue is to measure the photocurrent response as a function of excitation energy, comprising the spectral range which only excites low lying CT states.…”
mentioning
confidence: 99%
“…Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state . A popular method to address this issue is to measure the photocurrent response as a function of excitation energy, comprising the spectral range which only excites low lying CT states.…”
mentioning
confidence: 99%
“…Low temperature processed PSC grain boundaries, defect related electron diffusion or ion migration limits V oc . Poor interface or aging effect related extraction instability addressed in several recent reports . IEM band edge alignment to the active materials and contact metals work function influence in ESC are reported in numerous studies .…”
Section: Introductionmentioning
confidence: 99%
“…High EP of PSC material resolves either low exciton binding energy or nonexcitonic carrier separation that enhances V oc by implementing coherent interface layer . Energy conversion route, greater EP ropes to hot CT state for optical gain that ultimately enhances stability and efficiency of PSC and OSC . Advanced IEM band edge, EP, and greater conduction supports to enrich V oc and minimizes instability .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations